Clinical experience of trainees of The Royal Australian and New Zealand College of Obstetricians and Gynaecologists in insertion of long‐acting reversible contraceptives. (30th March 2021) - Abdalla, Orit; Black, Kirsten; Bateson, Deborah; Woods, Cindy; de Costa, Caroline
Abstract : Background: Long‐acting reversible contraceptives (LARCs) include both progestogen‐containing implants and intrauterine devices releasing either a progestogen or copper, providing highly effective contraception. Increasing uptake of LARCs is advocated by governments and professional organisations as an important strategy to reduce unintended pregnancy; such uptake requires, among other measures, adequate training of doctors in the areas of obstetrics and gynaecology and women's health. Aims: To assess The Royal Australian and New Zealand College of Obstetricians and Gynaecologists (RANZCOG) trainees' (Fellowship, Diploma or Certificate of Women's Health) experience and training in insertion and removal of LARCs. Materials and methods: An invitation email to participate in an anonymous survey approved by the Continuing Professional Development Committee of RANZCOG was sent to all current RANZCOG trainees in the three categories. The responses were categorised and analysed. Results: Of 1686 invited trainees, 294 (17.4%) responded: 250 in Australia and 44 in New Zealand; 127 were undertaking Fellowship training (8.3% of those invited) and 166 (100% of those invited) were undertaking training for the Diploma (either DRANZCOG and DRANZCOG Advanced) or the Certificate of Women's Health. Significant numbers of all categories of trainees had no or limited experience of insertion or removal of LARCs of all types and/or lacked self‐confidence in LARC provision. Conclusion: RANZCOG needs to address this training deficiency to continue as the leader in Australia in the provision of women's reproductive healthcare.